Protective Effect of Poria Cocos Polysaccharides on Fecal Peritonitis-Induced Sepsis in Mice Through Inhibition of Oxidative Stress, Inflammation, Apoptosis, and Reduction of Treg Cells - Wu, Yu; Li, Dai; Wang, Han; Wan, Xiaojian (Frontiers in Microbiology, 2022)
This study was conducted to investigate the potential pharmacological effects of Poria cocos polysaccharides (PCPs) on fecal-induced peritonitis (FIP) mice. Consequently, the fecal peritonitis (FP)-induced septic mice with the higher levels of tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), IL-1β, malondialdehyde (MDA), myeloperoxidase (MPO), histopathological lesion and bacterial burden, and lower levels of superoxide dismutase (SOD) and glutathione (GSH). Interestingly, PCP pre-treatment reduced inflammatory cytokines and oxidative stress in plasma and spleen and improved the resistance to FIP. Inflammatory infiltration and cell death in thymus or splenic tissue were alleviated with PCP pretreatment. Furthermore, Treg cells were moderated in the spleen with PCP pre-administration. In addition, PCP pretreatment downregulated Annexin-V in the thymus of FP-induced septic mice, and apoptosis of splenic cells was dose-dependent. In conclusion, PCPs have pharmacological and biological effects on FP-induced septic mice, and its molecular mechanism is related to antioxidative, anti-inflammation, anti-apoptosis, and the reduction of Treg activity in splenic cells.